1999
DOI: 10.1128/mcb.19.6.4143
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Single-Stranded DNA and Destabilization of Telomeric Repeats in Yeast Mutant Strains Carrying a Deletion of RAD27

Abstract: The Saccharomyces cerevisiae RAD27 gene encodes the yeast homologue of the mammalian FEN-1 nuclease, a protein that is thought to be involved in the processing of Okazaki fragments during DNA lagging-strand synthesis. One of the predicted DNA lesions occurring in rad27 strains is the presence of single-stranded DNA of the template strand for lagging-strand synthesis. We examined this prediction by analyzing the terminal DNA structures generated during telomere replication in rad27 strains. The lengths of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 59 publications
9
103
1
2
Order By: Relevance
“…Mutations in genes involved in replication of the lagging strand (Pol␣, RAD27) cause an increase in the amount of telomeric single-stranded DNA (ssDNA) (24,36). We examined the telomeric ssDNA in rad24, ctf18, rfc1, and elg1 mutants and found no accumulation of ssDNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in genes involved in replication of the lagging strand (Pol␣, RAD27) cause an increase in the amount of telomeric single-stranded DNA (ssDNA) (24,36). We examined the telomeric ssDNA in rad24, ctf18, rfc1, and elg1 mutants and found no accumulation of ssDNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Suggesting that telomeric localization implies a telomeric function for Dna2, we have shown that dna2-2 est1⌬ mutants, lacking telomerase activity, senesce much more rapidly than est1⌬ mutants, and dna2-2 est1⌬ mutants show altered pathways of telomerase-independent survival (14). dna2 mutants have normal or slightly long telomeres, but overproduction of DNA2 leads to increased occurrence of single-stranded regions at telomeres (17,39). Figure 6 compares telomere length in wild-type, pif1⌬, and dna2⌬ pif1⌬ strains.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this, the involvement of Dna2 with regard to telomere homeostasis was demonstrated in S. cerevisiae (51) and S. pombe (52). In addition, it was reported that Fen1 is also involved in telomere homeostasis (32). Therefore, it is likely that Mph1 is capable of stimulating both nucleases functions in telomere homeostasis.…”
Section: Discussionmentioning
confidence: 99%